Creativity – the Important Pedagogical Problem - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 1999)
The article aims to disclose the significance and some trends of creativity education. We present the results of teenagers creativity and pedagogical precondition, which can influence this phenomena.